2016
DOI: 10.21037/cco.2016.08.04
|View full text |Cite
|
Sign up to set email alerts
|

Does hepatitis B virus infection cause breast cancer?

Abstract: Lifestyle and family history are two of the most important risk factors for breast cancer (BC). However, these risk factors cannot explain the differences in the incidence and early BC onset among Chinese females compared to their western counterparts. We propose in this hypothesis the potential mechanism of indirect oncogenesis of hepatitis B virus (HBV) in causing BC through its persistence as occult infection and continuous replication with long term subtle liver damage. Estrogen is mainly deactivated in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 0 publications
0
14
0
Order By: Relevance
“…The mechanism of hepatitis B virus (HBV) and breast cancer progression and prognosis is unclear, but reports have shown that HBV infection is a risk factor for breast cancer 50 . The mechanism may be related to the interference of hepatitis B virus X protein (HBx) on cell repair mechanism, which leads to cell carcinogenesis 51 . In addition, HBV infection causes liver dysfunction, which affects estrogen regulation, and estrogen is a known risk factor for breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism of hepatitis B virus (HBV) and breast cancer progression and prognosis is unclear, but reports have shown that HBV infection is a risk factor for breast cancer 50 . The mechanism may be related to the interference of hepatitis B virus X protein (HBx) on cell repair mechanism, which leads to cell carcinogenesis 51 . In addition, HBV infection causes liver dysfunction, which affects estrogen regulation, and estrogen is a known risk factor for breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…This may explain to some extent that the observation of chronic HBV infection in this study mainly affects the prognosis of luminal BC, rather than other subtypes. Secondly, HBV may also directly affect breast cells through the action of oncoprotein HBV X protein (HBX) (21)(22)(23). For example, several studies have found that BC tissue highly expresses the oncoprotein HBXIP, a protein that interacts with HBX (24).…”
Section: Discussionmentioning
confidence: 99%
“…Genotype 1b is the most common globally (46%) [2], whereas genotype 6 is predominant in Southeast Asia [6]. In fact, the distribution of HCV genotypes is closely related to the pathway of virus transmission and human migration [7]. Therefore, the characterization of HCV genotypes correlates with both clinical features (natural history and therapy) and epidemiology [8].…”
Section: Introductionmentioning
confidence: 99%